Peer-mentorship and first-year inclusion: building belonging in higher education - Gisela J. van der Velden; John A.L. Meeuwsen; Christine M. Fox; Cecily Stolte; Gönül Dilaver (BMC Medical Education, 2023)
Abstract Background An inclusive academic environment is pivotal to ensure student well-being and a strong sense of belonging and authenticity. Specific attention for an inclusive learning environment is particularly important during a student’s transition to higher education. At Utrecht University’s Medical School, explorative interviews with students from minority groups indicated they did not always feel included during the orientation programme of their academic education. We, therefore, developed a bias awareness training with theoretical and practical components on diversity and inclusion for peer-mentors who are assigned to each first-year student at the start of university. Methods At the end of the orientation programme, we investigated the effectiveness of the training for two consecutive years using two measurements. Firstly, we investigated the behavioural changes in the peer-mentors through a (self-reporting) questionnaire. Additionally, we measured the perceived inclusion of the first-year students, divided into belonging and authenticity, using a validated questionnaire. Results Our results show that peer-mentors found the training useful and indicated it enabled them to create an inclusive atmosphere. Overall, students experienced a high level of inclusion during the orientation programme. After the first year, the bias training was adjusted based on the evaluations. This had a positive effect, as mentors felt they were significantly more able to provide an inclusive orientation in the second year of this study. In line with this, students experienced an increased level of authenticity specifically due to the peer-mentor in the second year as compared to the first. Conclusions We conclude that training peer-mentors is an effective way to increase awareness and to ensure an inclusive atmosphere during the start of higher education.